Procyanidin displayed a synergistic effect with roxadustat on renal anemia in mice - Cui, Mingyang; Wang, Zhe; Shi, Jiaxin; Wu, Wenbin; Tao, Jin; Han, Yujing; Yang, Zihui; Luo, Junjie; Luo, Yongting; An, Peng; Sun, Mingyue (Frontiers in Pharmacology, 2025)
IntroductionChronic kidney disease (CKD) often leads to renal anemia, a complication traditionally treated with erythropoiesis-stimulating agents (ESAs) and iron supplementation. However, these treatments may increase cardiovascular risks. Procyanidin, a compound found in black goji berries and mulberries, has known kidney-protective properties. This study aimed to explore the synergistic effects of procyanidin and roxadustat in alleviating renal anemia in CKD.MethodsA mouse model of CKD was induced by administering adenine, followed by treatment with procyanidin (250 mg/kg/day), roxadustat (5 mg/kg/day), or both. The effects on erythropoiesis, kidney function, iron metabolism, and inflammation were assessed through hematological analyses, histopathology, and gene expression profiling.Results Procyanidin alone improved erythropoiesis, kidney function, and reduced renal injury. Roxadustat enhanced erythropoiesis and iron metabolism but showed no significant effect on kidney function. The combination of both compounds resulted in superior improvements in hematological parameters, reduced kidney injury, fibrosis, and inflammation, and enhanced iron mobilization and absorption. Notably, procyanidin mitigated the thrombopoiesis induced by roxadustat.DiscussionThe combination of procyanidin and roxadustat provides a promising therapeutic approach for renal anemia by improving erythropoiesis, kidney function, and iron metabolism while reducing adverse effects, such as thrombosis. These findings suggest that procyanidin may enhance the safety and efficacy of roxadustat in CKD-related renal anemia. Further studies are needed to optimize treatment regimens for clinical application.